Evaluation of The Antidepressant-like Effect of The Aqueous Extract of Prunus Mahaleb L. Seed kernels in Mice - Awatif M. Al-Saaedi, (University of Thi-Qar Journal of Science, 2021)
Depression is a common psychiatric condition where 21% of the world population suffers from it. Prunus mahaleb is widely used in folk medicine to treat many diseases, but the antidepressant effect of this plant is not well investigated. The present study aims to evaluate the antidepressant-like activity of the aqueous extract of Prunus mahaleb seed kernels. For assessment of the antidepressant effect of aqueous extract of Prunus mahaleb at 200 and 400mg/kg, two models for depression were used in this study, forced swim test and tail suspension test. Aqueous extract of Prunus mahaleb seed kernels has a significant (p< 0.05) antidepressant-like effect at two doses 200 and 400 mg/kg in mice. Herbal medicine can play a significant role in treating depression; however, further studies are necessary to detect the pure compounds in Prunus mahaleb extract that responsible for the antidepressant activity and to understand their mechanism of action.